A Unified Theory of Weakly ${G}$-Closed Sets and Weakly ${G}$-Continuous Functions - Noiri, Takashi; Popa, Valeriu (Sarajevo Journal of Mathematics, 2024)
We introduce the notion of weakly $mng$-closed sets as a unified form of weakly $ω$-closed sets \cite{Ra}, weakly $rg$-closed sets \cite{Na}, weakly $π g$-closed sets \cite{RGC} and weakly $mg^*$-closed sets \cite{No-Po4}. Moreover, we introduce and study the notion of weakly $mng$-continuous functions to unify some modifications of weakly $g$-continuous functions. 2010 Mathematics Subject Classification. 54A05, 54C08